Roles of Candida albicans Gat2, a GATA-Type Zinc Finger Transcription Factor, in Biofilm Formation, Filamentous Growth and Virulence - Du, Han; Guan, Guobo; Xie, Jing; Sun, Yuan; Tong, Yaojun; Zhang, Lixin; Huang, Guanghua (PLOS ONE, 2012)
Candida albicans is the most common human fungal pathogen, causing not only superficial infections, but also life-threatening systemic disease. C. albicans can grow in several morphological forms including unicellular yeast-form, elongated hyphae and pseudohyphae. In certain natural environments, C. albicans also exists as biofilms, which are structured and surface-attached microbial communities. Transcription factors play a critical role in morphogenesis and biofilm development. In this study, we identified four adhesion-promoting transcription factors (Tec1, Cph1, Ume6 and Gat2) by screening a transcription factor overexpression library. Sequence analysis indicates that Gat2 is a GATA-type zinc finger transcription factor. Here we showed that the gat2/gat2 mutant failed to form biofilms on the plastic and silicone surfaces. Overexpression of GAT2 gene promoted filamentous and invasive growth on agar containing Lee's medium, while deletion of this gene had an opposite effect. However, inactivation of Gat2 had no obvious effect on N-acetyl-glucosamine (GlcNAc) induced hyphal development. In a mouse model of systemic infection, the gat2/gat2 mutant showed strongly attenuated virulence. Our results suggest that Gat2 plays a critical role in C. albicans biofilm formation, filamentous growth and virulence.